If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 + -8x + 4x = 27 Combine like terms: -8x + 4x = -4x -25 + -4x = 27 Solving -25 + -4x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + -4x = 27 + 25 Combine like terms: -25 + 25 = 0 0 + -4x = 27 + 25 -4x = 27 + 25 Combine like terms: 27 + 25 = 52 -4x = 52 Divide each side by '-4'. x = -13 Simplifying x = -13
| 18-2n=14 | | 3x-2-7=133 | | 331=6s+7 | | 7-3(x+4)= | | 8/3+3m/8=85/24 | | -2x-123-10x=93 | | 5x-(4x-1)=21 | | 9a=2a+4 | | 6y+8+4y=-3 | | 9/2*-1/9 | | 6-x=156 | | 8x+5-3x=2x-7 | | 0.75+x=12.25 | | 13v-38=14 | | 24+7=4x-9 | | 3(2.6+4.2x)=3.3x | | X+y=77.5 | | 5-3(x-7)= | | 11x-84-6x=56 | | 25=100/x2 | | 4x+7=2x+-7 | | 8x(x-5)=5x+12 | | 2x^2-13+6=0 | | (8/c)-c=7 | | 83=3x | | 5x+8-2x=18+7x | | 2.4*(0.7)= | | (10-3t)=t+4 | | c=400-5x+0.125 | | 2y=-1/2y-40 | | 6x-2-5x=0 | | 8-6x+2=4x-10 |